Analisis Kelembagaan Dan Strategi Peningkatan Daya Saing UMKM Emping Melinjo Di Kabupaten Magetan - Fajar Kurnia Mustaqim; Kusnandar Kusnandar; Agustono Agustono (Universitas Sebelas Maret, 2018)
This study aims to analyze institutional melinjo chips MSMEs, identify internal and external factors, formulate strategies for improving the competitiveness of melinjo chips MSMEs, and prioritizing strategies for improving the competitiveness of melinjo chips MSMEs in Magetan regency. The research methods used include: Descriptive Analysis, SWOT Analysis, SWOT matrix, and AHP. The results showed that: (1) there are 4 structure of the supply chain in the distribution of products chips melinjo, and the main institutional sectors in improving the competitiveness of melinjo chips MSMEs, namely the public sector, voluntary sector and private sector; (2) identification of internal and external factors obtained strengths, weaknesses, opportunities and threats in improving the competitiveness of melinjo chips MSMEs; (3) matrix SWOT produced 10 alternative strategies to increase competitiveness; (4) priority strategy in improving the competitiveness of melinjo chips MSMEs is provide training and guidance to the next generation about the importance of business continuity that has quality products according to market demand, establish cooperation with suppliers to ensure theavailability of raw materials; and improve product quality and maximum service to maintain consumer confidence.